2004
DOI: 10.1038/sj.cdd.4401419
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide generated at the level of mitochondria in response to peroxynitrite promotes U937 cell death via inhibition of the cytoprotective signalling mediated by cytosolic phospholipase A2

Abstract: We have studied the relationships existing between delayed formation of H 2 O 2 and activation of cytosolic phospholipase A 2 (cPLA 2 ), events respectively promoting toxicity or survival in U937 cells exposed to peroxynitrite. The outcome of an array of different approaches using phospholipase A 2 inhibitors, or cPLA 2 antisense oligonucleotides, as well as specific respiratory chain inhibitors and respiration-deficient cells led to the demonstration that H 2 O 2 does not mediate toxicity by producing direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 38 publications
10
28
0
Order By: Relevance
“…Products of either 5-lipoxygenase (5-7) or cyclooxygenase (9), extensively released at the inflammatory sites, initiate a cascade of events culminating in Bad phosphorylation and thus in its cytosolic accumulation. In addition, under these conditions, Bax is also retained in the cytosol and the cells preserve their ATP pool (27), thereby surviving regardless of the damage accumulated (3)(4)(5)(6)(7)9). In particular, our work performed in U937 cells provided evidence of survival of cells with extensive DNA strand scission (27,28).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Products of either 5-lipoxygenase (5-7) or cyclooxygenase (9), extensively released at the inflammatory sites, initiate a cascade of events culminating in Bad phosphorylation and thus in its cytosolic accumulation. In addition, under these conditions, Bax is also retained in the cytosol and the cells preserve their ATP pool (27), thereby surviving regardless of the damage accumulated (3)(4)(5)(6)(7)9). In particular, our work performed in U937 cells provided evidence of survival of cells with extensive DNA strand scission (27,28).…”
Section: Discussionmentioning
confidence: 58%
“…We showed that the resistance phenotype is dependent on the ability of these cells to respond to peroxynitrite with the triggering of a survival signaling in which cytosolic phospholipase A 2 , 5-lipoxygenase, and protein kinase C␣ are sequentially involved (3)(4)(5)(6), leading to Bad phosphorylation and to its cytosolic accumulation (5)(6)(7). Loss of mitochondrial Bad creates optimal conditions for the antimitochondrial permeability transition function of Bcl-2/Bcl-x L (8).…”
Section: Differentiation-associated Loss Of Ryanodinementioning
confidence: 99%
“…The question we ask has an additional important implication because complex III inhibitors promote rapid necrotic U937 cell death after exposure to otherwise non-toxic concentrations of peroxynitrite (Tommasini et al, 2002a;Tommasini et al, 2004a), thus suggesting that cell demise might also take place via a Ca 2+ -independent mechanism. This would be an interesting observation especially if necrosis takes place via a mitochondrial permeability transition (MPT)-dependent mechanism, as previously noticed using intrinsically toxic levels of peroxynitrite (Sestili et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…macrophages), surviving to peroxynitrite regardless from the damage accumulated (20,26). DNA damage mediated by peroxynitrite in these cells under inflammatory conditions is indeed of importance in carcinogenesis (27).…”
Section: Implications For Cell Survivalmentioning
confidence: 99%
“…In this direction, it is important to point out that these cells are resistant to peroxynitrite as they are able to respond with a signaling pathway, sequentially involving cytosolic phospholipase A 2 , 5-lipoxygenase and PKCa, promoting Bad phosphorylation (11,(20)(21)(22)(23). In other words, these cells, as well as cells belonging to the monocyte/macrophage lineage, including human monocytes and macrophages (23)(24)(25)(26), while committed to mitochondrial permeability transition by peroxynitrite, nevertheless survive by promoting the cytosolic localization of Bad, an event creating optimal conditions for the cytoprotective effects of Bcl-2/BclX L .…”
Section: Implications For Cell Survivalmentioning
confidence: 99%